Evaluation of Shear Bond Strength of Composite to Feldspathic Porcelain after Porcelain Surface Treatment with CO2 and Er:YAG lasers - Mehdi Shirinzad; Reza Fekrazad; Loghman Rezaei-Soufi; Ebrahim Yarmohammadi; Shahriar Jalalian (Islamic Dental Association of Iran, 2013)
Background and Aim : Fractured ceramic crowns can sometimes be repaired with composite resin. The aim of the current study was to determine the shear bond strength of composite to feldspathic porcelain after CO2 and Er:YAG laser porcelain surface preparation .   Materials and Methods : In this in-vitro study, 36 feldspathic porcelain blocksmeasuring 1*10*10 mm were divided into 3 groups of 12. Porcelain surfacesinthe first and second groupswere treated with 1.8W CO2 laser and 5W Er:YAG laserirradiation, respectively. Third group specimens were subjected to 9.5% hydrofluoric acid surface conditioning. Allgroups received application ofsilane and adhesiveafterwards. A composite cylinder with 3.5 mm diameter and 5 mm height was bonded to specimens. In order to evaluate the shear bond strength,aUniversal Testing Machine withacrosshead speed of 1 mm/min was used. Statistical analysis was performed using one-way ANOVA and Tukey's HSD test and P<0.05 was considered statistically significant .   Results : The mean shear bond strength values (MPa) were 13.03±2.57%, 12.02 ±3.4 and 19.23±4.62, for the first, second and third groups respectively. One-way ANOVA revealed a statistically significant difference in this respect between the three groups (P< 0.001).    Tukey's HSD testdemonstratedsignificant differences betweenthefirst and third groups (P= 0.000) as well as the second and third groups (P=0.000). However, no significant difference was detected betweenthe first and second groups (P =0.778).   Conclusion : Consideringthe study results, CO2or Er:YAG laser irradiationis not suggested as an appropriate alternative to hydrofluoric acid for surface preparationoffeldspathic porcelain.